MANAJEMEN PEMBELAJARAN BERBASIS BLENDED LEARNING PADA MASA PANDEMI COVID-19: Studi Kasus di Akademi Manajemen Administrasi Yogyakarta - Fahlefi, Wilis (Jurnal Ilmu Manajemen dan Akuntansi Terapan (JIMAT), 2021)
During the Covid-19 Pandemic, educational institutions carried out distance learning online. For areas that are included in the green zone, face-to-face learning can be carried out with a limited time and comply with health protocols. One of the learning innovations that can be carried out by educational institutions is blended learning-based learning, including at the Yogyakarta Administrative Management Academy. This study aims to determine learning planning, implementation of learning, and evaluation of learning based on blended learning at the Yogyakarta Administrative Management Academy. The study used a qualitative approach with descriptive methods. Data were obtained through observation, interviews, and documentation studies. The results showed that at the planning stage, the two Yogyakarta AMA with the blended learning model during the Covid-19 pandemic were supported by existing facilities and infrastructure. In the implementation phase, AMA Yogyakarta applies a group division system. Some groups are offline and some are online learning. However, conditions changed very quickly, Yogyakarta became a red zone so it was not allowed to carry out face-to-face learning. At the evaluation stage, AMA Yogyakarta conducted a website-based online evaluation.